On-demand spectrum sharing by flexible time-slotted cognitive radio networks - Chen, Xu (2013)
In this paper, we present a novel framework for spectrum sharing in cognitive radio networks. The secondary users (SUs) can share the spectrum resource with primary users (PUs) in a cooperative manner, where PUs trade their information and surplus resource, and SUs access the primary spectrum intelligently based on SUs' heterogeneous demands and PUs' resource prices. After paying PUs a subscription fee for the spectrum information, SUs become spectrum-aware and avoid the overhead on spectrum sensing. During SUs' channel access, PUs further charge SUs based on the amount of resource taken by SUs. We model this sharing problem in a flexible time-slotted structure, where SUs' decisions include the selection of proper transmission channel and slot length to meet their demands. This joint decision problem is studied as a spectral temporal allocation game. We prove the existence of a Nash equilibrium and design a strategy update process which can converge to an equilibrium.